IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KABUPATEN DILI TIMOR-LESTE - Armindo Soares (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
This study aims (1). Describing and Analyzing the Implementation of the Regulation of the Minis-ter of Home Affairs of Timor-Leste Number 33 of 2008 in Dili Regency of Timor-Leste, and (2) De-scribing and Analyzing what are the supporting factors and inhibiting factors in the implementa-tion of the Regulation of the Minister of Home Affairs of Timor-Leste Number 33 In 2008 in Dili Regency, Timor-Leste, which was analyzed using the implementation theory of Edward III (1980), with 4 variables that influence the implementation of a policy, namely: communication, resources, disposition, and bureaucratic structure. The method used in this study is a quali-tative research method with a qualitative descriptive approach. The results of this study indicate that the implementation of the Waste Management Policy in Dili Regency, Timor-Leste has not all of the processes of implementing waste management running well, such as communi-cation variables and resources that have not been running well, and optimally.